BePresent Universal Internet-Based Parenting Intervention: Single-Arm Pre-Post Intervention Study - Mishina, Kaisa; Baumel, Amit; Kinnunen, Malin; Ristkari, Terja; Heinonen, Emmi; Hinkka-Yli-Salomäki, Susanna; Sourander, Andre (Germany, 2025)
Background: Internet-based parenting programs have great potential to promote positive parent-child relationships as well as to reach and engage parents.
Objective: This study aimed to assess the universal internet-based BePresent parenting intervention for families with 3-year-old children and how it influences the child's behavior and daily-life situations assessed by parents. The first aim of the study was to assess the change from baseline to follow-up in child hyperactivity and conduct problems, affective reactivity, and daily activities. The second aim was to assess intervention completion rates. The third aim was to evaluate parent satisfaction with the intervention. The fourth aim was to assess all outcomes by comparing those who completed the intervention and those who did not.
Methods: We conducted a single-arm pre- and postintervention study. Parents attending their child's 3-year health check-up were recruited from children's health clinics. The intervention was an unguided internet-based parenting program consisting of 5 modules. Self-reported measures were collected at baseline and at an 8-week follow-up. Linear mixed-effects models were used to analyze the changes from baseline to follow-up.
Results: Altogether, 752 parents registered, and 515 started the intervention. Of those, 36% (n=183) completed the intervention. Parents reported high satisfaction with the intervention: the majority (68.8%-84.9%) were satisfied with various aspects of the program, and 89.9% said the intervention provided information about positive parenting skills. The findings show significant decreases with small effect sizes in parents' ratings of child hyperactivity (P=.03; d=0.12) and conduct problems (P=.001; d=0.20) between baseline and the 8-week follow-up. A similar finding was observed in the parent ratings of child irritability (P≤.001; d=0.27) using the Affective Reactivity Index. Parents reported improvement in the daily functioning of their child when it was measured with a questionnaire adapted from the Barkley Home Situations Questionnaire (P=.01; d=0.14).
Conclusions: Universal digital interventions have the potential to be implemented widely in community settings to improve knowledge and positive parenting skills. However, there is a need to assess the efficacy of digital universal interventions using randomized controlled designs and to examine additional ways to increase adherence to universal programs.